2018
DOI: 10.29289/2594539420180000377
|View full text |Cite
|
Sign up to set email alerts
|

Axillary surgery in breast cancer: acute postoperative complications in a hospital cohort of women of Rio de Janeiro, Brazil

Abstract: Analisar a incidência de complicações pós-operatórias precoces em mulheres com câncer de mama de acordo com a cirurgia axilar. Métodos: Estudo observacional de uma coorte de mulheres diagnosticadas com câncer de mama em estágio clínico T1-T2N0M0 atendidas no Instituto Nacional de Câncer do Brasil de janeiro de 2007 a dezembro de 2009. O desfecho foi definido como complicações pós-cirúrgicas no membro superior afetado, tais como: síndrome da rede axilar, escápula alada, parestesia e ferida cirúrgica, seroma e i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
9
0
4

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 26 publications
0
9
0
4
Order By: Relevance
“…Nesse sentido, os pacientes oncológicos apresentam alta incidência de edemas, linfedemas, trombose venosa profunda e outras alterações, como a síndrome da rede axilar, dor e complicações da ferida operatória, que podem estar relacionadas também com a piora da qualidade de vida dessa população [3][4][5][6][7][8] .…”
Section: Introductionunclassified
“…Nesse sentido, os pacientes oncológicos apresentam alta incidência de edemas, linfedemas, trombose venosa profunda e outras alterações, como a síndrome da rede axilar, dor e complicações da ferida operatória, que podem estar relacionadas também com a piora da qualidade de vida dessa população [3][4][5][6][7][8] .…”
Section: Introductionunclassified
“…Therefore, early diagnosis during initial staging can lead to greater cure chances and lower treatment-associated morbidity. However, diagnoses in Brazil are still regularly performed in more advanced stages, requiring more aggressive therapeutic approaches and resulting in increased morbidity and increased incidence of functional, emotional, and social sequelae, directly compromising patient's quality of life [4][5][6] .…”
Section: Introductionmentioning
confidence: 99%
“…In a prospective cohort study carried out at the Brazilian National Cancer Institute (INCA-Brazil) concerning women undergoing axillary lymphadenectomy (AL), lymphedema incidence was reported as 17% in 2 years, 30% in 5 years, and 41% in 10 years 12,13 . Macedo et al 6 performed an observational study comprising 933 women (73.2% submitted to sentinel lymph node biopsy [SLB], 15.4% submitted to SLB followed by AL, and 11.4% submitted to AL) and concluded that SLB represents an independent protective factor concerning complications, including lymphedema, when compared to AL 14 .…”
Section: Introductionmentioning
confidence: 99%
“…Kanserden kurtulan bireyler tedavi sonrası hastalık ve tedavilerin psikososyal ve fiziksel sorunlarıyla baş etmeye çalışmakta, yaşam kalitesini istenilen düzeyde sürdürememe endişesi yaşamaktadırlar 11 . Hastalar tedavi sonrası yaşadıkları psikososyal sorunların [12][13][14] yanı sıra seroma 15 , hematom 16 , aksiller web sendromu 17 , post mastektomi ağrı sendromu 18 , fantom meme ağrısı 19 , eklem ağrıları 20 , yara enfeksiyonu 21 , etkilenen ekstremite hareket kısıtlılığı 22 , yorgunluk 12 , uyku problemleri 23 ve lenfödem 15 gibi fiziksel sorunlarla baş etmek durumundadırlar.…”
Section: Introductionunclassified